A Study to Assess the Impact of Lockdown on Physical and Psychosocial Health among Senior Citizen in the Selected Areas of Pune City - Tejashri Ligade , Deepak Sethi, Priyanka Kadam3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Over the previous few weeks, the COVID pandemic has impacted lives across the world in unimaginableways, and quite ever at now like this, it’s essential we concentrate to our elderly who are theforemost vulnerable segment of the population. With aging, immunity decreases making elderly more proneto the virus.Additionally, the general public above the age of 60 have some or the opposite medical conditionlike diabetes, hypertension or asthma; all of which are risk factors.1 The demographic pyramid of India isshifting fast with a more number of within the elderly population. It appears that the socio-economic andsocio cultural transformation to higher individual freedom, hedonism, family unit, feminism, materialismetc. is catching older generation unaware. Aims: within the above context, the target of the study was tospot the themes that are related to the standard of life of home-dwelling elderly. In fact, the time of the 2011census there have been around 104 million people above the age of 60, which implies that a staggering9 percent of our population fall within this high risk group. But besides being most in danger, socialdistancing and therefore the nationwide lockdown even have implications on mental state of the elderly,which simply shouldn’t be ignored.2Methods: A non-experimental descriptive survey method was used accustomed assess the impact of lockdownon physical and psychological health of grownup selected by purposive sampling. The information wascomposed by pretested questionnaire. Data analysis was carried out with level of significance.Results: 60 senior citizen participated in the study.58% were not satisfied with lock down as it is affectingtheir physical and mental health. Impact is more on age group of 60 years and above.Conclusions: The present study showed unsatisfied impact of lockdown among senior citizens. Lockdownhas affected them in all physical, social and psychological way. It is necessary to take measures to relievetheir stress due to lockdown.